2015
DOI: 10.2967/jnumed.115.160739
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Targeting the Gastrin-Releasing Peptide Receptor, Somatostatin Receptor 2, or Chemokine C-X-C Motif Receptor 4 in Breast Cancer for Imaging and Therapy

Abstract: Imaging and therapy using radioligands targeting receptors overexpressed on tumor cells is successfully applied in neuroendocrine tumor patients. Because expression of the gastrin-releasing peptide receptor (GRPR), somatostatin receptor 2 (SSTR2), and chemokine C-X-C motif receptor 4 (CXCR4) has been demonstrated in breast cancer, targeting these receptors using radioligands might offer new imaging and therapeutic opportunities for breast cancer patients. The aim of this study was to correlate messenger RNA (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
(32 reference statements)
5
28
1
Order By: Relevance
“…When we associated receptor mRNA expression levels of primary BCs and metastases with clinico-pathological factors, we observed a significantly higher GRPR and SSTR2 expression in both ESR1 -positive primary BC and metastases. These findings are in agreement with our previous findings [10] and findings by Kumar et. al.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…When we associated receptor mRNA expression levels of primary BCs and metastases with clinico-pathological factors, we observed a significantly higher GRPR and SSTR2 expression in both ESR1 -positive primary BC and metastases. These findings are in agreement with our previous findings [10] and findings by Kumar et. al.…”
Section: Discussionsupporting
confidence: 95%
“…Prior to this, we evaluated whether mRNA expression levels of tumor tissue properly represent radioligand binding, by correlating in vitro autoradiography results with mRNA expression levels of selected primary tumors and corresponding metastases with varying mRNA receptor expression. In line with previously published findings [10], we demonstrated that there was a high correlation between mRNA expression of the receptors and radiotracer binding, which suggests that mRNA expression levels can be used as a surrogate for radiotracer binding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since BC is a very heterogeneous disease, SSTR expression between BC subtypes may vary. We and others showed higher SSTR expression in ER-positive BC compared to ER-negative BC, identifying ER-positive BC subtypes as the most suitable subtypes for SSTR-mediated imaging [68,69,70,71]. If we only focus on these BC subtypes, which account for the majority of the breast tumors, SSTR-mediated BC imaging might be more successful.…”
Section: Somatostatin Receptor (Sstr)-mediated Bc Imagingmentioning
confidence: 99%
“…GRPR is also expressed in lymph node metastases from breast cancer, whereas the GRPR expression level in normal lymph node tissue is very low. In addition, GRPR mRNA levels are correlated with smaller pathologic tumor size, positive estrogen receptor 1, progesterone receptor status and negative HER2 status [11,12].…”
mentioning
confidence: 99%